Accuracy of Bone Resection in MAKO Total Knee Robotic-Assisted Surgery - Sires, James D.; Craik, Johnathan D.; Wilson, Christopher J. (The Journal of Knee Surgery, 2019)
Accurate component positioning and planning is vital to prevent malalignment of total knee arthroplasty (TKA) as malalignment is associated with an increased rate of polyethylene wear and revision arthroplasty. The MAKO total knee robotic arm-assisted surgery (Stryker, Kalamazoo, MI) uses a preoperative computed tomography scan of the patient's knee and three-dimensional planning to size and orientate implants prior to bone resection. The aim of this study was to determine the accuracy of the MAKO Total Knee system in achieving the preoperative plan for bone resection and final limb coronal alignment. A series of 45 consecutive cases was performed using the MAKO Total Knee system and Triathlon Total Knee implant (Stryker) between April 2018 and May 2019. The difference between what was planned and what was achieved for bone resection and coronal limb alignment was calculated. A total of 37 patients had their data captured using the MAKO system software. Mean difference from the plan for distal femoral cuts was 0.38mm (0.32) deep/proud, anterior femoral cuts 0.44mm (0.27) deep/proud and tibial cuts 0.37mm (0.30) deep/proud. In total, 99 out of 105 (94.29%) of bone resections were within 1mm of the plan. Mean absolute difference in final limb coronal alignment was 0.78° (0.78), with 78.13% being ≤1.00° of the plan, and 100% being ≤3.00° of the plan. The accuracy in achieving preoperatively planned bone resection and final limb coronal alignment using the MAKO Total Knee system is high. Future research is planned to look at whether this is associated with decreased rates of polyethylene wear and revision arthroplasty.
Keywords: total knee arthroplasty; bone resection; robotic-assisted; MAKO; accuracy